Akuszerka na ziemiach polskich w świetle przepisów oraz literatury medycznej z końca XVIII i pierwszej połowy XIX wieku = The midwife on Polish territory in the light of the laws and medical literature of the late 18th century and the first half of the 19th century - Kurowska, Hanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The end of the 18th century was a crucial period in the history of Polish obstetrics. The medical knowledge was made available also to the women. Especially for them midwifery courses were organised from 1773, during which received theoretical and practical knowledge. The largest centers were located in Kraków, Warsaw, Vilnius, Poznan and at first also in Lviv. They were made in its form as a result of an order of the authorities of Prussia, Austria and Russia, which required that the new schools were established, often with free fee for part of the students.
Keywords: czasopismo; czasopismo akademickie; Ziemie Zachodnie; stosunki polsko-niemieckie; pogranicze polsko-niemieckie; historia